Chemical kinetic modeling of diethoxymethane oxidation: A carbon–neutral fuel. (1st May 2021) - Li, Runzhao; Herreros, Jose Martin; Tsolakis, Athanasios; Yang, Wenzhao
Graphical abstract: Fig. Comparison of major oxidation pathways between DEM and n-heptane. Highlights: A detailed chemical kinetic mechanism for DEM oxidation is developed. Current mechanism includes the low and high temperature reactions to extend application domain. Current mechanism is validated against ignition delay times and laminar flame speeds. DEM is more reactive at low temperature than n-heptane favoring advanced combustion modes. DEM ignition delay time decreases with increasing temperature and NTC behavior is weak. Abstract: Diethoxymethane (DEM) is a carbon–neutral fuel with high cetane number (57.3). A detailed chemical kinetic mechanism for DEM oxidation covering low and high temperature reactions is first developed in this work. The reaction scheme and rate rules of DEM sub-mechanism are determined by the analogy method to n-heptane. Aramco 3.0 mechanism is used as a base mechanism to consider C0-C4 fuels while dimethoxymethane mechanism is included to ensure the mechanism compatibility and rate rule consistency. Thermodynamic and transport properties of new species in DEM sub-mechanism are computed by the methods of group additivity and properties correlation. The mechanism is validated against ignition delay times and premixed laminar flame speed measured by shock tube, rapid compression machine and spherical flame in combustion vessel. The verification covers a pressure range of 2 30 bar, an equivalence ratio range of 0.5 2.0, a temperature range of 540 1371 K. A satisfactory agreement between the experimental and computed results is observed, supporting the proposed reaction scheme and rate rules. Comparison of the ignition delay times between DEM and n-heptane indicates: (i) DEM is more reactive at low temperature (500 670 K) than n-heptane which favors low temperature combustion mode. (ii) DEM ignition delay times demonstrate monotonous temperature dependence at the full temperature regime but it is relatively independent of temperature at intermediate temperature (620 960 K). Therefore, a negative temperature coefficient (NTC) behavior is not observed in most conditions. (iii) DEM may not be an efficient chemical ignition source compared to n-heptane due to insufficient temperature increases and active radical accumulation.